2000
DOI: 10.1055/s-2000-6770
|View full text |Cite
|
Sign up to set email alerts
|

The Design, Synthesis and Conformation of Some Newβ-Hairpin Mimetics: Novel Reagents for Drug and Vaccine Discovery

Abstract: Syntheses and conformational studies are presented of some novel templates for use in the construction of b-hairpin mimetics. The templates are relatively rigid molecules that constrain the backbone conformation of an attached peptide loop into the bregion of f/y-space. They include diketopiperazines incorporating substituted proline derivatives, as well as heterochiral diproline units, which can be incorporated efficiently into cyclic peptide bhairpin mimetics by solid-phase methods. Potential applications of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 32 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Robinson and co-workers developed a bicyclic building block that can can similarly occupy one of the hairpin turns of antiparallel-β-sheet-like cyclic peptides (e.g., 163 , Figure ). Compound 163 is notable because the opposing hairpin turn contains the sequence Asn–Pro–Asn–Ala, a key pharmacophore of a malaria protein that is potentially important for vaccine development. Suich and co-workers showed that a biaryl linker can take the place of one of the hairpin turns of the canonical two-turn hexapeptide structure ( 164 , Figure ).…”
Section: The Effect Of Structural Modification On the Conformations O...mentioning
confidence: 99%
“…Robinson and co-workers developed a bicyclic building block that can can similarly occupy one of the hairpin turns of antiparallel-β-sheet-like cyclic peptides (e.g., 163 , Figure ). Compound 163 is notable because the opposing hairpin turn contains the sequence Asn–Pro–Asn–Ala, a key pharmacophore of a malaria protein that is potentially important for vaccine development. Suich and co-workers showed that a biaryl linker can take the place of one of the hairpin turns of the canonical two-turn hexapeptide structure ( 164 , Figure ).…”
Section: The Effect Of Structural Modification On the Conformations O...mentioning
confidence: 99%